Two Sources of Meaningful Life: Aesthetics and Ethics - Bielskis, Andrius; Mardosas, Egidijus (Problemos, 2016)
In this paper, we analyse two alternative approaches to the question of a meaningful life in contemporary philosophy: the aesthetic and the ethical. First, we examine Michel Foucault’s aesthetic approach whereby he argues in favour of understanding life as a work of art. Here aesthetics is understood as a constant search for the new, as innovation, and discontinuity. Next we examine the ethical approach found in contemporary neo-Aristotelianism developed by Alasdair MacIntyre. The ethical approach is presented as a direct critique of Nietzcheanism and aims to reconstruct the ethical subject in terms of unity, continuity, and the good. By examining the relation between the two positions, we argue for the importance of neo-Aristotelian ethics in the postmodern condition.